Low Divergence Coherently Coupled Vertical Cavity Surface Emitting Laser Ring Arrays - Nusrat Jahan; Katherine A. Lakomy; Pawel Strzebonski; B. J. Thompson; K. D. Choquette (IEEE Photonics Journal, 2022)
We report the theory and experimental verification of a method to reduce beam divergence from coherently-coupled ring arrays of photonic crystal vertical cavity surface emitting lasers (VCSELs). The photonic crystal etched into the top distributed Bragg reflector defines the optically coupled array elements, each of which has independent current injection and thus independent gain. Using a 2-dimensional complex waveguide model we simulate the supermodes of a 6-element ring array of VCSELs. The influence of the photonic crystal, free carrier loss, laser gain, and carrier-induced index suppression arising from the spatially defined gain regions are included in our analysis. Our simulations show the latter enables preferred anti-guided supermodes with reduced beam divergence. Optical characterization of the spectral and beam characteristics of 6-ring photonic crystal implanted VCSEL arrays shows that when the arrays are current-tuned to quasi-single mode operation, we find the beam divergence angle approaches 2° consistent with our simulations. This method of reduced beam divergence may have advantages for high-brightness applications.